DNA precipitation revisited: A quantitative analysis. Issue 3 (28th July 2021) - He, Shupeng; Cao, Bozhi; Yi, Yi; Huang, Shenhao; Chen, Xiao; Luo, Sheng; Mou, Xiaoyu; Guo, Tong; Wang, Yujie; Wang, Yanwei; Yang, Guangcan
Abstract: We have quantitatively investigated the precipitation of DNA in different valence cations and in various ethanol concentration solution. In free ethanol condition, monovalent ion cannot induce DNA condensation and in turn to precipitation. Divalent ion can cause DNA precipitation as the concentrations of both Mg 2+ (MgCl2 ) and Ca 2+ (CaCl2 ) go up to a critical value of about 50 mM. After adding ethanol, monovalent ion and divalent ion can promote DNA precipitation significantly, but it has no effect on the process by trivalent ions. In monovalent ion solution of 100 mM, the critical volume ratio of ethanol is about 52% for DNA precipitation. However, the value decreases significantly to 4% in 25 mM divalent ion solution. Based on the precipitation curves, we quantitatively calculated the binding energies between the cations and phosphate group of DNA. For monovalent ions and in aqueous solution, the Na + ‐DNA binding energy is about −5.52 KJ·Mol −1 (−2.63 kB T, the precipitation temperature is 253 Kelvin) and the K + ‐DNA binding energy is about −4.77 KJ·Mol −1 (−2.27 kB T). For divalent ions and in the same condition, the Ca 2+ ‐DNA binding energy is about −8.25 KJ·Mol −1 (−3.93 kB T) and the Mg 2+ ‐DNA binding energy is about −8.67 KJ·Mol −1 (−4.13 kB T). The scenario of DNA precipitation modulation by ethanol and zwitterionic ions is demonstrated by atomic force microscopy (AFM) imaging intuitively. Abstract : DNA condensation or precipitation by cations depends on their valences, concentrations and solvents. If the binding energy between DNA and cations reaches a critical value 4 kB T, DNA condensation or precipitation occurs.